PENGARUH PERILAKU PEMIMPIN DAN PEMBAGIAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA DINAS KESEHATAN PROVINSI GORONTALO - Sri Meike Jusup; Pemy Christian; Poppy Muzijat (AkMen JURNAL ILMIAH, 2022)
This study aims to determine the effect of leader behavior and division of labor on the work effectiveness of employees at the Gorontalo Provincial Health Office either simultaneously or partially, by taking 69 employees as research samples. Data collection techniques using questionnaires and using multiple regression as a method of data analysis and using the SPSS version 21 application. Based on the results of hypothesis testing, it was revealed that simultaneously leader behavior and division of labor had a positive and significant effect on the work effectiveness of employees at the Gorontalo Provincial Health Office with a large influence, namely 0.966 or 96.6%. partially the leader's behavior has a positive and significant effect on the work effectiveness of employees at the Gorontalo Provincial Health Office with a large effect of 0.435 or 43.5% and the division of labor partially has a positive and significant effect on the work effectiveness of employees at the Gorontalo Provincial Health Office of 0.549 or 54.9%. there are variables that are not examined but have an effect that is equal to 0.034